2002
DOI: 10.1121/1.1423926
|View full text |Cite
|
Sign up to set email alerts
|

Speech dynamic range and its effect on cochlear implant performance

Abstract: This study examines optimal conversions of speech sounds to audible electric currents in cochlear-implant listeners. The speech dynamic range was measured for 20 consonants and 12 vowels spoken by five female and five male talkers. Even when the maximal root-mean-square (rms) level was normalized for all phoneme tokens, both broadband and narrow-band acoustic analyses showed an approximately 50-dB distribution of speech envelope levels. Phoneme recognition was also obtained in ten CLARION implant users as a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
0
6

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(127 citation statements)
references
References 27 publications
8
113
0
6
Order By: Relevance
“…60 dB (Fig. 10B), which is consistent with a previous report (Zeng et al 2002). A change in the IDR does not change the acoustic peak amplitudes that are mapped to the subjects' most comfortable levels.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…60 dB (Fig. 10B), which is consistent with a previous report (Zeng et al 2002). A change in the IDR does not change the acoustic peak amplitudes that are mapped to the subjects' most comfortable levels.…”
Section: Resultssupporting
confidence: 92%
“…The dynamic range of typical speech sounds is between 30 and 60 dB (Zeng et al 2002). The speech processor must fit speech sounds into this narrow dynamic range for CI users.…”
Section: Experiments 3: Effects Of Amplitude Compressionmentioning
confidence: 99%
“…These results led the authors to conclude that a 30-dB IDR provides adequate speech information for phoneme identification, even when spectral resolution is restricted to four spectral channels. More recently, Zeng et al (2002) measured the effects of IDR on vowel and consonant recognition in Clarion cochlear implant users with the CIS strategy, for IDR settings ranging from 10 to 60 dB. In contrast to the Fu and Shannon results, these authors found that IDRs of 50 to 60 dB yielded the highest scores for consonant recognition in quiet, and that IDRs of 40 to 50 dB yielded the highest scores for vowel recognition in quiet.…”
Section: Discussionmentioning
confidence: 42%
“…This was consistent with the results from the previous study. 71 For sentences in noise, there was no significant difference in scores for the 3 IIDRs. However, subjective preferences showed that some subjects found the 56-dB IIDR uncomfortable in everyday listening environments.…”
Section: Instantaneous Input Dynamic Rangementioning
confidence: 96%
“…Recent studies by Zeng et al 71 showed that the acoustic dynamic range was 46 dB for vowels and 47 dB for consonants. When vowel and consonant perception in CI recipients was tested in quiet, an IIDR of approximately 50 dB gave the optimum vowel and consonant scores.…”
Section: Instantaneous Input Dynamic Rangementioning
confidence: 99%